Suitability of the depression, anxiety, and stress scale in Parkinson's disease - Johnson, A.; Lawrence, B.; Corti, E.; Booth, L.; Gasson, Natalie; Thomas, M.; Loftus, Andrea; Bucks, R. (I O S Press, 2016)
© 2016 IOS Press and the authors. All rights reserved. Background: The Depression, Anxiety, and Stress Scale 21 (DASS-21) is a frequently used measure of emotional disturbance symptoms in Parkinson s disease (PD). However, the factor structure of the DASS-21 in PD has yet to be explored. Objective: To assess whether the scale is measuring these symptoms in PD in the same way as the general population. Methods: The present study fit a series of established DASS-21 factor structures with both confirmatory factor analysis (CFA) and exploratory structural equation modelling (ESEM) using data from 251 participants with PD. Results: The 3-factor ESEM provided the best fit. The depression and stress scales fit well, however, few items on the anxiety subscale loaded clearly, with several items significantly loading onto the depression or stress factors. Conclusions: Whilst the depression and stress subscales appear suitable in PD, poor loadings and internal consistency indicate the anxiety subscale may not accurately assess anxiety symptomology in PD. This may be due to the scale s reliance on physiological symptoms as indicators of anxiety, when many of these are present in PD. Thus, the anxiety subscale of the DASS-21 may not be a suitable measure of anxiety in PD.